The Image of Bengkulu City Government in Public Service Delivery as Reflected in Online Media Coverage From 2023 To 2025 - Antonio Imanda; Martha Heriniazwi Dianthi; Dahlia; Dyah Noor Intan (CV. Era Digital Nusantara, 2026)
This study aims to analyze the image of the Bengkulu City Government in public service delivery as reflected in online media coverage from 2023 to 2025. The research uses a descriptive qualitative approach with qualitative content analysis. The data were obtained from online news articles discussing public service programs of the Bengkulu City Government, particularly the Harapan dan Doa Public Service Mall, Mobile Public Service Mall, digital public services, the Sippadek application, free licensing services, and the public service compliance assessment by the Ombudsman. The findings show that online media tend to construct a positive image of the Bengkulu City Government as an active, responsive, transparent, and adaptive local government in improving public services. The Public Service Mall appears as the dominant narrative because it represents integrated and accessible service delivery. In addition, the increasing number of service users, the implementation of mobile services, and the development of digital-based services strengthen the image of innovation and service improvement. However, the study also finds that the image presented in online media is mostly built from official government sources and institutional achievements. Public voices, service user experiences, and critical evaluations of service quality are less dominant in the news coverage. Therefore, the public service image of the Bengkulu City Government in online media can be understood as a positive institutional image, but it does not fully represent the complete experience of citizens in accessing public services.